Pemanfaatan Active Learning untuk Mengembangkan Higher Order Thinking Skills (HOTS) dalam Pembelajaran Pendidikan Agama Islam: Suatu Studi Literatur - Wulandari, Safira Laila; Maulana, Ikhwan; Zaman, Nurul (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study was motivated by the need to improve the quality of Islamic Religious Education (IRE) learning so that it does not only focus on delivering material but also encourages students to actively build understanding through higher-order thinking processes. Traditional teacher-centered learning tends to limit students' analytical, evaluative, and creative abilities. Therefore, this study aims to analyze the use of Active Learning in IRE and its relationship with the development of Higher Order Thinking Skills (HOTS). The method used was library research with a Systematic Literature Review (SLR) approach, which involved identifying, selecting, and synthesizing various relevant literature from the last ten years. The results of the study showed that Active Learning was implemented through various strategies such as problem-based learning, project-based learning, think-pair-share, the use of digital technology, and collaborative discussions. These strategies shift the focus of learning from the teacher to the students so that they can construct knowledge through dialogue, reflection, and problem solving. The findings also show that this approach has a direct influence on the development of HOTS, especially the ability to analyze religious issues, evaluate arguments based on arguments, and create contextual solutions in learning situations. In addition to improving cognitive abilities, Active Learning has an impact on increasing learning motivation, courage to ask questions, active involvement, and the quality of students' social interactions. The implications of this study confirm that PAI learning needs to integrate Active Learning strategies.